INTERLINGUAL AND INTRALINGUAL ERRORS IN DESCRIPTIVE WRITINGS - Afi Ni'amah; Ika Lusi Kristanti (LPPM Universitas PGRI Jombang, 2024)
Writing in English is not easy that students need to be assisted. However, stumbling upon errors in writing is common among students that the value of error correction must be taken into account. Error analysis is a process used to identify the learning objectives attained by students in creating an inter language system. This study set out to determine the primary cause of the errors that seventh-grade students made when writing descriptive essays. Al-Khresheh’s (2010) theory was used in finding interlingual errors and Richard’s (1974) theory for intralingual errors. When writing descriptively, students make a variety of intralingual and interlingual mistakes. Interlingual error so includes literal translation, mother tongue interference, and transfer error. On the other hand, intralingual errors include oversimplification, disregard for rule limitations, partial rule application, and incorrect concept hypothesis. The results demonstrate that intralingual error—specifically, incomplete rule applications—and interlingual error—specifically, literal translation and interference from the mother tongue—are the primary causes of errors. In this instance, teachers must help students better grasp the laws of the target language when they are composing texts. More research on student writing errors should take into account the gender and genre of content being studied.